FLYPAPER EFFECTPADA BELANJA PEMERINTAH DAERAHDI PROVINSI MALUKU UTARA - Suratni Amiro (Jurnal Manajemen Sinergi, 2015)
expenditure flypaper effect In North Maluku Provincial Government. Commissionsupervising the Abdul Hadi Sirat and commission supervising two Irvan Zam Zam. The purpose ofthe study was to analyze the effect of local revenue (PAD) and the General Allocation Fund (DAU)of the Local Government Expenditure North Maluku province, as well as analyze the phenomenonof flypaper. Object of this study is all kabupeten/ cities in North Maluku province except the island ofMorotai, and the focus of research is the realization of the budget year report 2004-2011. Thepopulation in this study is the province of North Maluku and the sample was 8 districts/ cities exceptthe island of Morotai, the analysis used is multiple linear regression analysis using SPSS. The resultsof this study, the first to show that the variable revenue (PAD) does not significantly influence theLocal Government Expenditure and General Allocation Fund significantly influence the LocalGovernment Expenditure. Both the value of Standardized Coefficients revenue (PAD) is not greaterthan the value of the Standardized Coefficients General Allocation Fund (DAU), and only the GeneralAllocation Fund (DAU) significantly affects Expenditure. This means that the flypaper on LocalGovernment Expenditure.